A size switchable nanoplatform for targeting the tumor microenvironment and deep tumor penetration. Issue 21 (17th May 2018) - Cun, Xingli; Li, Man; Wang, Shuying; Wang, Yifei; Wang, Jialing; Lu, Zhengze; Yang, Ruixin; Tang, Xian; Zhang, Zhirong; He, Qin
Abstract : This study established an MMP-2/pH dual-sensitive, multistage nanoparticle, DGL/DOX@PP, that can release small nanoparticles through the simple breakage of an enzyme-sensitive bond. Abstract : The complex tumor microenvironment (TME) in solid tumors forms physiological barriers to the efficient delivery of nanomedicine, leading to limited therapeutic efficacy. Herein, to overcome these physiological barriers and improve the therapeutic effect, we constructed a novel size-adjustable nanoplatform for efficient drug delivery into solid tumors. The smart size-switchable nanoplatform (DGL/DOX@PP) was prepared by conjugating small dendrigraft poly-l -lysine (DGL) to poly(ethylene glycol)–poly(caprolactone) micelles via a matrix metalloproteinase 2 (MMP-2)-sensitive peptide. DGL/DOX@PP had an initial size of 100 nm and a nearly neutral charge, rendering the system able to take advantage of the enhanced permeability and retention effect. After extravasation from the tumor vessels, small DGL/DOX nanoparticles (∼30 nm) were rapidly released from DGL/DOX@PP in response to MMP-2 in the TME. This process of particle size alteration greatly enhanced the nanoparticle penetration into both multicellular spheroids (MCSs) and solid tumors. In vivo results demonstrated that compared with small and non-switchable nanoparticles, particles from the size-switchable nanoplatform achieved excellent antitumor efficacy in 4T1 tumor-bearing mice. This size-adjustable nanoplatform provides a multifunctional strategy for TME modulation and tumor penetration.